The Substitution of Fresh Moringa Leaves and Moringa Leaves Powder on Organoleptic and Proximate Characteristics of Pudding - Mia Srimiati; Lina Agestika (Amerta Nutrition, 2022)
Background: Moringa Oleifera leaves "Marungga" contain fiber, vitamins, minerals, and polyphenol compounds that potential to fulfill nutritional requirements among children and adults. The product development often utilized Moringa leaves powder rather than the fresh ones. The powdering process might reduce the nutritional content while using fresh Moringa leaves is more applicable for the local community. However, the strong taste and aroma of Moringa leaves could influence the individual acceptance of a food product. Pudding is a simple and easy-to-make food product at the household level. Purpose: This study aimed to compare the effectiveness of fresh Moringa leaves substitution compared with Moringa leaves powder on pudding product acceptance and proximate characteristics. Methods: This was an experimental study with a complementary randomized design. The substitution of fresh Moringa leaves was 0%,20%,30%, while Moringa leaf powder was 0%, 5%, 10%. We conducted an organoleptic test, hedonic test, and proximate analysis of chosen formulations. Statistical analysis included Analysis of Variance (ANOVA), Duncan's multiple range test, and t-test. Results: The chosen formula based on the hedonic test was the 20% of fresh Moringa leaf substitution (FML2) with a score of 3.64, and 5% of Moringa leaf flour (FMP1) with a score of 4.10. A significant difference between the two formulations was their texture; FMP1 had a hard texture than FML2. The protein, fat, carbohydrate, and total calorie content of those formulations were significantly different, but not for the ash content. Conclusion: Substitution used fresh leaves utilized more Moringa leaves and improved pudding nutrients contents than powder type.